Nutritional status and quality of life in diabetic patients on hemodialysis: a cross-sectional study from Palestine - Eba'a Hafi; Ro'ya Soradi; Sarah Diab; Ahmad M. Samara; Marah Shakhshir; Malik Alqub; Sa'ed H. Zyoud (BMC, 2021)
Abstract Background End-stage renal disease (ESRD) is a leading cause of death and morbidity worldwide. Malnutrition is a common problem among hemodialysis (HD) patients that negatively impacts their prognosis and is linked to an increase in morbidity and mortality in these patients, as well as a decrease in their quality of life (QOL). In this study, we aimed to evaluate the QOL and to investigate factors that can influence it, including nutritional status, as well as socio-demographic factors, among Palestinian diabetic patients on HD therapy. Methods This was a cross-sectional study that occurred at a large hemodialysis center in Palestine. Malnutrition was assessed by the malnutrition-inflammation scale (MIS), and the quality of life was evaluated by using the EuroQoL five-dimensional instrument (EQ-5D). Multivariable linear regression analysis was carried out to look at the effect of multiple variables on QOL. Results A total of 118 diabetic patients on HD were included. Of these, 66.9% were male, and 60.2% were aged 60 years or higher. Having multiple comorbid diseases (p=0.004) and having been on HD for >4 years (p=0.003) were significantly associated with a higher MIS score, whereas living alone (p=0.037) and having been on HD for >4 years (p=0.002) was significantly associated with lower EQ-5D score. We also observed a significant association between the MIS score and the EQ-5D score(r=−0.616, p<0.001). Multiple linear regression analysis demonstrated that diabetic hemodialysis patients who lived within a family household were positively correlated with the QOL score (standardized coefficient, 0.178; 95% confidence interval (CI), 0.042 to 0.372; p = 0.015), and MIS score was significantly and negatively correlated with QOL scores (standardized coefficient, −0.587; 95% CI, −0.047 to −0.028; p < 0.001). Conclusions We found that malnutrition was associated with a lower QOL score among diabetic patients on HD. We recommend general practitioners, dietitians, nephrologists, and nurses to make plans that pay more attention to this group of patients who show evidence of malnutrition. Patients on dialysis for ≥ 4 years, patients who live alone, and those suffering from multiple co-morbid diseases should receive special care due to their higher risk of being impacted by this problem.